Hajj Product Differentiation Strategy at Bank Muamalat KC Kediri in Facing Competition from Other BPS BPIH - Raharto, Reneshin Dwi Raharto Putri; Damayanti, Susi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research objective: The objective of this research is to analyze and identify the product differentiation strategy of Bank Muamalat KC Kediri's Hajj. Design/Method/Approach: This study uses a descriptive qualitative approach method. The object of this study is Bank Muamalat KC Kediri located at Jl. Sultan Hasanuddin No.26, Dandangan, Kec. Kota, Kediri City, East Java 64122. The data collection techniques used are direct observation at Bank Muamalat KC Kediri, in-depth interviews with related parties and documentation, namely by collecting data from journal articles and websites that are relevant to the research topic. Data triangulation is carried out by comparing findings from various sources to increase the validity and reliability of the results. Data analysis is carried out through reduction, presentation, and drawing conclusions in accordance with the qualitative approach applied in this study. Research Findings: This study found that Bank Muamalat KC Kediri implemented a differentiation strategy. Hajj products through one-stop service , flexibility scheme payment , and waiting period program based on deposit contribution . Bank Muamalat targets three main segments of hajj pilgrims and designs strategies based on understanding their characteristics and needs to create superior value, increase customer loyalty, and attract new pilgrims. Bank Muamalat has succeeded in strengthening its position as a leader in the hajj ecosystem in Kediri and building a strong foundation for future market expansion. Theoretical contribution/Originality: This study contributes to the development of literature on product differentiation strategies in the Islamic banking sector, particularly in Hajj services. Practitioner/Policy Implications: This study provides guidance for other Islamic banks to increase competitiveness by developing differentiation strategies, innovative services that are in accordance with market needs. Research limitations: This study has limitations in the scope of the location that only focuses on the Kediri area and does not discuss the impact of the strategy in the context of the national market. In addition, this study has not explored customer perceptions in depth regarding the features offered.